Adsorpsi Karbon Aktif Dari Tempurung Kluwak (Pangium edule) Terhadap Penurunan Fenol - Abdul Rahman Arif; Asri Saleh; Jawiana Saokani (Al-Kimia, 2015)
Relative concentration of phenol was increased with concomitant increase in the industry that produced phenol. It coused by level of phenol contamination in water rise was increased also. It was needed waste handling specialy for phenol waste. One of way in processed phenol waste was adsorption processed by using activated carbon. Pangium edule could be use as media of making activated carbon to decrease organic compounds specialy for phenol because pangium edule contained the element of carbon that was potential as activated carbon. Carbonization process was conducted by drum clamp while activation that used was acid phosphate (H3PO4), calium hydroxide (KOH) and natrium carbonat (Na2CO3). The determination of phenol concentration dissolved used  spectrophotometer UV-Vis and then was tested with the Langmuir isotherm equation and Freundlich. The result of research  shown that the largest of phenol removal effeciency of activated carbon obtained by activated carbon with activator calium hydroxide (KOH) on carbon doses 1,5 gram was 91,97% with phenol opening 300 mg/L.